Effects of a plant extract from Ruptiliocarpon caracolito on the growth and differentiation of P19 mouse embryonal carcinoma cells - Aghsani, Parisa (University of Ottawa (Canada), 2004)
Present data indicate that the Ruptiliocarpon caracolito extract exerted significant anti-proliferative activity against P19 EC cells, in the absence of toxicity and significant alterations in the differentiation status of the cells. The focus of this study was to determine whether the proliferation of P19 EC cells would decrease in response to Ruptiliocarpon caracolito extract and whether the anti-proliferative activity, if observed, would be accompanied by alterations in the cell differentiation status. According to the data obtained in the present study, the plant extract exerted a significant anti-proliferative activity against the P19 EC cell line. This activity was exhibited in a dose-related fashion. Amongst the doses tested (5--70mug/ml), concentrations ranging from 30--70mug/ml showed a significant anti-proliferative activity (P < 0.001). The highest growth reduction activity of the extract was noticed at a concentration of 50mug/ml of culture medium. Viability studies indicated that the decrease in cell proliferation was not secondary to the toxicity of the extract. (Abstract shortened by UMI.)
Keywords: Biology, Molecular.